Characterization of light-control-light system using graphene oxide coated optical waveguide - Ahmad, Harith; Soltani, Soroush; Ismail, Mohammad Faizal; Thambiratnam, Kavintheran; Chong, Wu Yi; Yasin, Moh (IOP Publishing, 2018)
An optical waveguide was coated with graphene oxide (GO) using the drop-casting technique to increase the interaction between the waveguide's evanescent field and the GO layer. Subsequently, a 1550 nm tunable laser source and 980 nm pump laser is used to study the potential of the GO-film to control the flow of light through the waveguide by altering the state of the waveguide between transparent (ON) and opaque (OFF). The GO layer has a thickness of 0.40 μm and allows a 1550 nm signal with a peak power of -7.0 dBm and average output power of 0 dBm to pass through at a maximum pump power of 60 mW. The waveguide has a responsivity of ∼0.1 dB mW-1, with the time to switch between the ON and OFF states being about 3 ms.